Universal basic income and the threat to democracy as we know it - Nelson, Peter (Economics collection., 2018)
Some of the greatest minds of the century have predicted that computers or artificial intelligence will replace 80 percent, if not more, of the world's workforce. The only uncertainty is the time frame, with the average prediction at about 30 years, although many believe it will be sooner. No matter the exact period, the impact on our planet will eventually be enormous because governments will still need to find a way to provide the unemployed with money on which to live and a Universal Basic Income (UBI), or something similar, is proposed to be paid to everyone without means test. That solution might appear well in theory, but the large numbers of unemployed will not want to be marginalized and will demand over time that the UBI be increased. Following human nature, under a democratic system as we know it, supposedly based on one person one vote, people will vote for whoever gives them more, and more, until the economic system breaks down, unable to afford the payments. The question is whether democracy will survive the challenge or whether we finish with a benign group of bureaucrats at the top who decide what is in the best interests of the majority and the rest of the global population simply accepts it.